SUBSTITUSI TEPUNG TAPIOKA DENGAN TEPUNG KULIT PISANG KEPOK (Musa Paradisiaca L.) TERHADAP KUALITAS ORGANOLEPTIK NUGGET AYAM BROILER - Wael, Monik; Liur, Isye Jean; Tiven, Nafly Comilo (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This research aims to determine the effect of substitution of tapioca flour and kepok banana peel flour on the organoleptic quality of broiler chicken nuggets. The research was carried out at the Animal Products Technology Laboratory, Faculty of Agriculture, Pattimura University. The number of respondents involved was 35 panelists. The research procedures included making kepok banana peel flour and making broiler chicken nuggets. The variables tested in this study included the organoleptic quality of broiler chicken nuggets, namely color, aroma, tenderness, texture and taste. The data obtained were analyzed using analysis of variance (ANOVA) using a Completely Randomized Design (CRD), with 5 treatments of kepok banana peel flour, each repeated 3 times. The research results show that tapioca flour and kepok banana peel flour can be used as alternative fillers which provide better organoleptic quality to broiler chicken nuggets, especially in terms of color, aroma, texture and taste.